Corruption Levels: Audit Findings and Financial Performance in Provincial Governments in Indonesia (E-Jurnal Akuntansi, 2026)
This study aims to examine the influence of local government financial performance, audit findings, and follow-up to audit recommendations on corruption levels in Indonesia. Furthermore, the study also examines the role of audit opinion as a moderating variable in strengthening or weakening the relationship between these variables and corruption levels. The population in this study covers all 38 provinces in Indonesia. Sampling was conducted using a purposive sampling method, resulting in 34 provinces as samples with a total of 208 observations during the 2018–2023 period. The results show that financial performance, as measured by the efficiency ratio, audit findings, and follow-up to audit recommendations, significantly influences corruption levels. Meanwhile, the Regional Financial Independence Ratio (RFI) does not significantly influence corruption levels. Regarding the moderating role of audit opinion, it was found that audit opinion was unable to strengthen the relationship between the Regional Financial Independence Ratio (RFI) and follow-up to audit recommendations on corruption levels. Conversely, audit opinion was proven to strengthen the relationship between the efficiency ratio and audit findings on corruption levels.
Keywords: Audit Findings; Financial Performance; Corruption